Ultrasound measurements reveal predictable relationship between spawning time and ovarian growth in Octopus vulgaris - Lorenzo Márquez; Pauline Weterings; Samar Saber; Beatriz C. Felipe; Sofia Maccuro; Marta Serrano; Eve Seuntjens; Francisco Acosta-Cifuentes; María González; Eduardo Almansa (Aquaculture Reports)
There has been a great interest in common octopus Octopus vulgaris aquaculture in recent years and commercial production is within reach. O. vulgaris is a short-lived semelparous species with a long spawning period. Therefore, monitoring ovary maturation in cultured octopuses can be useful in the scheduling of hatchery operations and management of culture resources. The present work assessed ovary volume as a proxy for maturity status in cultured and wild common octopus by means of a noninvasive technique, ultrasonography, to anticipate the time of spawning in aquaculture. A total of 27 octopuses (15 cultured females with initial wet weights from 600 to 4600 g, and 12 wild females weighing 990–4800 g) in different ovarian maturation stages were used in ultrasonographic procedures. Ultrasound-based ovary volumes were compared with real ovarian volumes and then the ultrasonography-based gonadosomatic index (GSIU) was estimated. Data from cultured females indicate that GSIU was initially below 0.3 cm3 per 100 g of body weight in immature animals, and attained a fast increase until reaching about 4.0 cm3 per 100 g of body weight just before spawning. The steep increase in relative volume occurred similarly in females of different body weights. Furthermore, the specific growth rate of cultured animals decreases with time, and with GSIU. Lastly, a linear mixed model indicated a significantly negative and logarithmic relationship between the time to spawning and GSIU in captive females. This relationship can be used to predict spawning time in immature and maturing females, helping in the management of octopus broodstock in research and production facilities.